A Comparison of Management Conditions in Japan’s Dental Clinics and Medical Clinics - Kawabuchi, Koichi; Kajitani, Keiko (UI Scholars Hub, 2015)
In recent years, national medical expenditures have continued to increase in Japan, and have now reached 39 trillion yen. In contrast, dental clinic expenditures have been slow to grow over the past few years, totaling 2.7 trillion yen. At the same time, the number of dentists continues to increase, with a total of 102,551 dentists in 2012, surpassing the 100,544 physicians at medical clinics. Objective: Given this, we compared management conditions at dental clinics and medical clinics over time to determine whether management conditions of dental clinics are really as harsh as often claimed. Methods: We used the relevant data provided in the Central Social Insurance Medical Council’s Survey on Economic Conditions in Health Care for statistics, which depicts management conditions at clinics, and analyzed the causes. Results: Annual fluctuations in the revenue/expense gap (revenue less expense) show that the gap for dentists far undercut that for physicians at medical clinics. The main reason for this decline in revenue is that the number of dental patients declined more than the unit price rose compared to the medical clinic. Conclusion: We determined that management conditions are harsh for dental clinics.